Self-efficacy, career development, and work engagement on employee performance: Evidence from aviation sector organizations - Joko Wiyanto; Dewi Juliah Ratnaningsih; Suratini Suratini (Journal of Enterprise and Development (JED), 2024)
Purpose — This research aims to test and analyze the influence of self-efficacy and career development on employee performance, while also examining the mediating role of work engagement.Method — This research employs an associative quantitative research approach. The research sample comprised 147 employees from the UPBU Class I offices in Mopah Merauke, Wamena, and Domine Eduard Osok Sorong. Probability sampling was used as the sampling technique. The analysis method utilized in this study is SEM-PLS, conducted using SmartPLS3 software.Result — We found that self-efficacy and career development have a positive and significant impact on work engagement. Furthermore, self-efficacy, career development, and work involvement positively and significantly affect employee performance. Our research also revealed that work involvement plays a mediating role in the influence of self-efficacy and career development on employee performance.Novelty  — This study innovatively utilizes work engagement as a mediating variable to delve into the determinants of work performance specifically within the context of local public organizations, shedding light on previously unexplored aspects of employee productivity in this setting.